2012
DOI: 10.2147/ijn.s32694
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interaction of folic acid conjugated superparamagnetic iron oxide nanoparticles and its use as contrast agent for targeted magnetic imaging of tumor cells

Abstract: Abstract:The purpose of the study was to develop tumor specific, water dispersible superparamagnetic iron oxide nanoparticles (SPIONs) and evaluate their efficacy as a contrast agent in magnetic resonance imaging (MRI). We have developed SPIONs capped with citric acid/2-bromo-2-methylpropionic acid which are compact, water dispersible, biocompatible having narrow range of size dispersity (8-10 nm), and relatively high T 2 relaxivity). The targeting efficacy of unconjugated and folic acid-conjugated SPIONs (FA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…As expected, a sharp decreased uptake of the nanoparticles by MDA-MB-231 cells was observed ( Figure 10 ). This result indicates that the uptake of Fe 3 O 4 @SiO 2 (FITC)/PEI-FA nanoparticles was mediated by folate receptor on the cell surface 9 38 . Taken together, these findings indicated that conjugation of Fe 3 O 4 @SiO 2 (FITC) nanoparticles with a tumor targeting agent, FA specifically, led to the increased targeted uptake of Fe 3 O 4 @SiO 2 (FITC)/PEI-FA nanoparticles by MDA-MB-231 cells bearing FA receptor.…”
Section: Resultsmentioning
confidence: 85%
“…As expected, a sharp decreased uptake of the nanoparticles by MDA-MB-231 cells was observed ( Figure 10 ). This result indicates that the uptake of Fe 3 O 4 @SiO 2 (FITC)/PEI-FA nanoparticles was mediated by folate receptor on the cell surface 9 38 . Taken together, these findings indicated that conjugation of Fe 3 O 4 @SiO 2 (FITC) nanoparticles with a tumor targeting agent, FA specifically, led to the increased targeted uptake of Fe 3 O 4 @SiO 2 (FITC)/PEI-FA nanoparticles by MDA-MB-231 cells bearing FA receptor.…”
Section: Resultsmentioning
confidence: 85%
“…Uptake of nanocomposites was determined by quantifying iron content in the cell by means of atomic absorption spectra (AAS) (Prijic et al 2010; Dinda et al 2012). MCF-7 were seeded in 6-well plates, at 7.2 × 10 6 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…The magnetic labeling of cells can be performed following either of two approaches: (i) the direct attachment of magnetic particles to the cell surface [ 21 ] or (ii) the receptor-mediated or transfection agent-mediated endocytosis pathway which internalizes biocompatible magnetic particles [ 16 ]. A variety of competent ligands and target agents conjugated onto nanoparticle surfaces, including monoclonal antibodies, transferrin, and folic acid, have been used to target cell surfaces [ 22 24 ]. The endocytosis pathway, which involves the transfection of IONPs into cells, requires a high rate of nanoparticle internalization by the cells.…”
Section: Introductionmentioning
confidence: 99%